Heat Acclimation and Inhibition of Cytokinin Degradation Positively Affect Heat Stress Tolerance of Arabidopsis - Prerostova, Sylva; Dobrev, Petre I.; Kramna, Barbara; Gaudinova, Alena; Knirsch, Vojtech; Spichal, Lukas; Zatloukal, Marek; Vankova, Radomira (Frontiers in Plant Science, 2020)
In order to pinpoint phytohormone changes associated with enhanced heat stress tolerance, the complex phytohormone profiles [cytokinins, auxin, abscisic acid (ABA), jasmonic acid (JA), salicylic acid and ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC)] were compared in Arabidopsis thaliana after direct heat shock (45°C, 3 h) and in heat-stressed pre-acclimated plants (1 h at 37°C followed by 2 h at optimal temperature 20°C). Organ-specific responses were followed in shoot apices, leaves and roots immediately after heat shock and after 24-h recovery at 20°C. The stress strength was evaluated via membrane ion leakage and the activity of NADPH oxidases (NOX) and antioxidant enzymes [superoxide dismutases, guaiacol peroxidases (POD), catalases, ascorbate peroxidases (APX)]. Heat acclimation diminished negative effects of heat stress, especially in apices and roots, no significant differences being observedin leaves. Low NOX1-3 activities indicated diminished production of reactive oxygen species. Higher activity of APX, POD1, and the occurrence of POD3-4 reflected acclimation-stimulated readiness of the antioxidant system. Acclimation diminished heat shock-induced changes of ABA, JA, cytokinin and auxin levels in apices. Excess of ABA catabolites suggested an early stress response. The strong up-regulation of ABA and ACC in roots indicated defense boost in roots of acclimated plants compared to the non-acclimated ones. To evaluate the possibility to enhance stress tolerance by cytokinin pool modulation, INCYDE-F, an inhibitor of cytokinin oxidase/dehydrogenase, was applied. As cytokinin effects on stress tolerance may depend on timing of their regulation, INCYDE was applied at several time-points. In combination with acclimation, INCYDE treatment had a slight positive effect on heat stress tolerance, mainly when applied after 2-h period of the optimal temperature. INCYDE increased contents of cytokinins trans-zeatin and cis-zeatin in roots and auxin in all tissues after heat shock. INCYDE also helped to suppress the content of ABA in leaves, and ethylene in apices and roots. INCYDE application to non-acclimated plants (applied before or after heat shock) strengthened negative stress effects, probably by delaying of the repair processes. In conclusion, pre-treatment with moderately elevated temperature enhanced heat stress tolerance and accelerated recovery after stress. Inhibition of cytokinin degradation by INCYDE slightly improved recovery of acclimated plants.